Sn Nanodots-Induced Composition Enhancement (NICE) to Achieve 26 at. % Sn in GeSn for Mid-Infrared Integrated Photonics. (22nd October 2019) - Cuervo Covian, Alejandra Vanessa; Zhou, Yiyin; Wang, Xiaoxin; Yu, Shui-Qing; Liu, Jifeng
Abstract : We present a nanodot-induced compositionenhancement (NICE) approach for achieving high Sn composition GeSn. The approach involves the deposition of Sn dots (20-60nm in diameter) using physical vapor deposition (PVD) with a subsequent deposition of a Ge capping layer and crystallization annealing. Photoluminescence at λ=3-4 μm is demonstrated towards mid infrared photonic applications.